CUSTOMER RELATIONSHIP MANAGEMENT AND INTEGRATED MARKETING COMMUNICATION INCREASE CUSTOMER LOYALTY IN SAVINGS BANKS IN BANDUNG - Taufik Zulfikar; Andika Satria Persada; Didin Saepudin (SEAN Institute, 2022)
The tighter competition between banks in the city of Bandung, the harder the bank's efforts to retain customers and get new prospective customers. Maintaining good relationships with customers with good marketing communication is also a way for banks to retain existing customers, while to get new customers the bank must be able to find out and fulfill what prospective customers want or need quickly and accurately. The formulation of the problem in this study is how the influence of customer relationship management and integrated marketing communications on customer loyalty either partially or jointly. The purpose of this study is to analyze and examine the effect of customer relationship management and integrated marketing communications on customer loyalty either partially or jointly. The research method used is quantitative where multiple linear regression is used as an analytical tool. Data obtained by survey method where the respondents as many as 200 people who are bank customers in the city of Bandung were given a questionnaire with closed questions. The results of the study with an error rate of 0.05 showed that there was a positive and significant effect of customer relationship management and integrated marketing communications on customer loyalty either partially or simultaneously, but the contribution of the two independent variables to the dependent variable with a coefficient of determination of 0.433 showed that there were still variables- other variables that were not examined that contributed 0.567 to customer loyalty.